SENSITIVITY AND SPECIFICITY OF PULSATILITY INDEX UMBILICAL ARTERY AND MIDDLE CEREBRAL ARTERY IN DETECTING INTRA UTERINE GROWTH RESTRICTION: Pulsatility Index - Nafees, Muhammad; Ibrahim, Muhammad Imran; Akram, Muhammad Hamid (Pakistan Armed Forces Medical Journal, 2014)
Objective: To determine the sensitivity and specificity of the pulsatile index in umbilical artery (PI-UA) and pulsatile index in middle cerebral artery (PI-MCA) in detecting IUGR by comparing it with the birth weight.Study Design: Validation study.Place and Duration of Study: Study was conducted in Department of Radiology, Military Hospital and Combined Military Hospital Rawalpindi, which was equipped with the (Aloka SSD-5500) using 3.5 MHz transducer after seeking permission from hospital ethical committee from 1st January 2010 to 10th July 2010.Subjects and Methods: Two hundred and fifty pregnant women with IUGR in third trimester were included in the study. Ultrasound estimation of fetal weight (using fetal biometry) below 10th percentile for that gestational age was labeled as IUGR. PI-MCA value of less than 11 was labeled as abnormal. PI-UA value of more than 1.451 was labeled as abnormal. Birth weight was taken as gold standard.Results: Sensitivity of PI-UA and PI-MCA were 94.8% and 79.8%, respectively. Specificity of PI-UA and PI-MCA were 36.8% and 90.7%, respectively.Conclusion: Raised PI value of UA is highly sensitive of IUGR; lower PI value of MCA is highly specific of IUGR and grave sign of fetal demise.